Insularity effects on the assemblage of the blood parasite community of the birds from the Gulf of Guinea. (11th July 2017) - Loiseau, Claire; Melo, Martim; Lobato, Elisa; Beadell, Jon S.; Fleischer, Robert C.; Reis, Sandra; Doutrelant, Claire; Covas, Rita
Abstract: Aim: Lower species diversity, increased population densities and ecological niche enlargement are common characteristics of island faunas. However, it remains to be determined if they extend to the parasite community. We tested if Haemosporidia parasite pressure varies between islands and the mainland with two different levels of analysis: (1) at the host community level and (2) with paired‐species comparisons between islands and the mainland. Location: Gulf of Guinea, West Africa. Methods: We used molecular‐based methods to identify avian Haemosporidian parasites ( Plasmodium, Haemoproteus and Leucocytozoon ) to describe their diversity, prevalence, host specificity and their phylogenetic relationships in five islands of the Gulf of Guinea and in nearby mainland areas. Results: We found reduced Haemosporidia diversity on islands for Haemoproteus and Leucocytozoon, but not for Plasmodium . In addition, lower parasite prevalence on islands was found using a paired‐species approach. Although the mean host specificity of the parasite community on islands did not differ from the mainland, we found a very distinct parasite species assemblage on the islands, which was composed of both the most generalist and the most specialist lineages. Main conclusions: This study supports the hypothesis that parasite pressure is reduced on islands. Colonization is made by generalists with high host switching capacities, with some subsequently evolving into highly specialized parasites. This suggests that "taxon cycle" dynamics may explain the assemblage of insular parasite communities.